Gambaran gaya hidup penderita hipertensi di puskesmas Pamolokan Kecamatan Kota Sumenep Kabupaten Sumenep tahun 2023 - Ulfa, Nadiyah; Purbowo Sintoro, Henry; Wibowo, Prajogo; Pratama A., Ronald (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Hypertension, a widespread global health issue, significantly contributes to the burden of non-communicable diseases. Its escalating prevalence globally and in Indonesia necessitates a comprehensive understanding of associated lifestyle patterns. This study, conducted at Pamolokan Health Center in Sumenep City District, Sumenep Regency, in 2023, focuses on the lifestyles of hypertensive patients. Globally, hypertension affects a substantial portion of the population, impacting public health significantly. In Indonesia, the prevalence of hypertension has steadily risen, prompting a focused examination of contributing factors. Among 85 hypertensive respondents, those aged 36-45 comprised 74.12%, with females constituting 76.67%. Hypertension severity varied, with 55.29% experiencing grade 1 hypertension. The study assessed lifestyle components, revealing 23.53% smoking, 67.06% favouring salty foods, 52.94% consuming fatty foods, 58.82% indulging in coffee, and 35.29% reporting regular physical activity. Understanding the lifestyle patterns of hypertensive patients is crucial for devising targeted interventions. This study's findings illuminate the interplay between age, gender, hypertension severity, and lifestyle choices. Insights contribute to the hypertension management and prevention discourse, emphasising the imperative of tailored public health strategies to address this global health challenge.